Diversity of flowering Plants of Dalma Wildlife Sanctuary, Jharkhand, India - Magesh, C. R.; Tiwari, Arjun Prasad; Rizvi, Naaz (Indian Forester, 2023)
The present work on flowering plants of Dalma Wildlife Sanctuary, Jharkhand reveals that a total number of 417 species under 317 genera belongs to 94 families, is recorded. Of these 62 species under 49 genera belonging to 14 families of Monocot and 350 species under 268 genera belongs to 78 families of Dicot.